Mesenchymal stem cells in the treatment of spinal cord injury: Mechanisms, current advances and future challenges - Xia, Yuanliang; Zhu, Jianshu; Yang, Ruohan; Wang, Hengyi; Li, Yuehong; Fu, Changfeng (Frontiers in Immunology, 2023)
Spinal cord injury (SCI) causes has a considerable impact on patient physical, mental, and financial health. Secondary SCI is accompanied by inflammation, vascular destruction, and subsequent permanent damage to the nervous system. Mesenchymal stem cells (MSCs) have anti-inflammatory properties, promoting vascular regeneration and the release neuro-nutrients, and have become a promising strategy for the treatment of SCI. Preclinical studies have confirmed that MSCs promote sensory and motor function recovery in SCI rats with encouraging results. In clinical trials, MSCs have been reported to improve the American Spinal Injury Association (ASIA) sensory and motor scores. However, the effectiveness of MSCs in treating patients with SCI remains controversial. MSCs promote tumorigenesis and ensuring the survival rate of MSCs in the harsh environment of SCI is challenging. In this article we examine the evidence on the pathophysiological changes occurring after SCI. We then review the underlying mechanisms of MSCs in the treatment of SCI and summarize the application of MSCs in clinical practice. Finally, we highlight the challenges surrounding the use of MSCs in the treatment of SCI and discuss future applications.